Plasmodium AdoMetDC/ODC bifunctional enzyme is essential for male sexual stage development and mosquito transmission - ALY, AHMED SAYED IBRAHıM; Hart, Robert J.; Ghaffar, Atif; Abdalal, Shaymaa; Perrin, Benjamin; Aly, Ahmed Sayed Ibrahım (My University, 2016)
Polyamines are positively-charged organic molecules that are important for cellular growth and division. Polyamines and their synthesizing enzymes are particularly abundant in rapidly proliferating eukaryotic cells such as parasitic protozoa and cancer cells. Polyamine biosynthesis inhibitors, such as Elfornithine, are now being considered for cancer prevention and have been used effectively against Trypanosoma brucei. Inhibitors of polyamine biosynthesis have caused growth arrest of Plasmodium falciparum blood stages in vitro, but in P. berghei only partial inhibition has been observed. While polyamine biosynthesis enzymes are characterized and conserved in Plasmodium spp., little is known on the biological roles of these enzymes inside malaria parasite hosts. The bifunctional polyamine biosynthesis enzyme S-adenosyl methionine decarboxylase/omithine decarboxylase (AdoMetDC/ODC) was targeted for deletion in P. yoelii. Deletion of AdoMetDC/ODC significantly reduced blood stage parasitemia but Anopheles transmission was completely blocked. We showed that male gametocytogenesis and male gamete exflagellation were abolished and consequently no ookinetes or oocyst sporozoites could be generated from adometdc/odc(-) parasites. Supplementation of putrescine and spermidine did not rescue the defective phenotypes of male gametocytes and gametes of the knockout parasites. These results highlight the crucial role of polyamine homeostasis in the development and functions of Plasmodium erythrocytic stages in the blood and in the mosquito vector and validate polyamine biosynthesis pathway enzymes as drug targeting candidates for malaria parasite transmission blocking.